Intra-inflorescence variations in floral morphological and reproductive traits of Iris sibirica L - Szőllősi, Réka (Acta Biologica Szegediensis, 2010)
Within inflorescences both temporal and spatial variations can be found in aspect of either attractive traits or reproductive organs. Morphological parameters of a flower depend on several factors like intra-plant position of the flower, other extrinsic and intrinsic factors, resulting in altered intra-inflorescence flower sizes or numbers, fruit set or seed set. In our study the sexual reproductive characteristics of Siberian Iris (Iris sibirica L.) were investigated, with special emphasis on how the floral morphological and reproductive traits vary spatially and temporally. We found that stalks typically had 2 levels and 5 flowers, and significant differences were found among individual flowers within the inflorescences. Flower diameter, sepaloid and petaloid tepal length and length of the filament significantly decreased with blooming order but none of the parameters showed significant correlation with the number of flowers per inflorescence. Pollen viability was above 90%, and did not dicrease with flowering order, which suggests that pollen production is independent of flower position. Parameters of female reproductive success such as ovule number and seed set per fruit also declined with flowering order, which was probably due to resource limitation within stalks or plants. Values of sex allocation (P/O ratios) refer to the type of breeding system of Iris sibirica.